Effects of low-temperature gel aging on the synthesis of zeolite Y at different alkalinities - Jülide Köroğlu, H.; Sarıoğlan, Alper; Tatlıer, Melkon; Erdem-Şenatalar, Ayşe; Tunç Savaşçı, Ö. (Elsevier BV, 2002)
The effects of low-temperature gel aging on the synthesis of zeolite Y were investigated. The variations occurring in the crystal sizes and size distribution as well as in the crystallinity and Si/Al ratio of the solid zeolite samples with aging time were determined for two different aging temperatures and two gel compositions in which the alkalinity was varied. It was determined that both the crystal sizes and the span of the size distribution may be decreased further by aging the gel at temperatures below room temperature. The alkalinity of the gel composition seemed to play a significant role in determining the magnitude of the effects of lowering the aging temperature on crystal sizes and the size distributions of the aged zeolite samples. The Si/Al ratio of zeolite Y was enhanced when the lower aging temperature and the less alkaline gel composition were used.